If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+9/13=2x-7
We move all terms to the left:
6x+9/13-(2x-7)=0
We get rid of parentheses
6x-2x+7+9/13=0
We multiply all the terms by the denominator
6x*13-2x*13+9+7*13=0
We add all the numbers together, and all the variables
6x*13-2x*13+100=0
Wy multiply elements
78x-26x+100=0
We add all the numbers together, and all the variables
52x+100=0
We move all terms containing x to the left, all other terms to the right
52x=-100
x=-100/52
x=-1+12/13
| 0=-16t^2+33t+9 | | 4(a+2)=8+4=a | | 3x+4x=35x= | | x=2+3+3x10 | | 15=6w-1 | | |3x-12|+4x=2x-2 | | 6u+17=10u-19 | | (x+8)⋅(x+9)= | | 17q+50=32q-100 | | N/3=2+n/5 | | 13j-1=8j+59 | | 80+9x=6(x+20) | | 3(2x-5)=2(3x-20 | | 4/5+x=1/3 | | 2(3x-5)=4(2x+6) | | 3x+2+112=90 | | 9z+10=6 | | 30a^2+3a=0 | | 8b-39=67b-98 | | 6-4y+3=2-5y | | 3q+36=12q-63 | | 10x-5=3(2x+2)+25 | | 40-9(x+4)+5x=-(4x-10) | | 5(2x-1)-4x-1=−12 | | 10h-64=11h-78 | | 7x+2=2(3x-4)x-10 | | 3(2x-3)+4(x+5)=8 | | 1. 8x+2=4x+10 | | -2/7*v=-10 | | 13s-83=4s+7 | | 4(2x-5)=6 | | 10h-47=6h-43 |